2020
DOI: 10.1523/jneurosci.1010-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Remarkable Regenerative Potential of the Dentate Gyrus Provided by Intrinsic Stem Cells

Abstract: Multiple insults to the brain lead to neuronal cell death, thus raising the question to what extent can lost neurons be replenished by adult neurogenesis. Here we focused on the hippocampus and especially the dentate gyrus (DG), a vulnerable brain region and one of the two sites where adult neuronal stem cells (NSCs) reside. While adult hippocampal neurogenesis was extensively studied with regard to its contribution to cognitive enhancement, we focused on their underestimated capability to repair a massively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…Hippocampal CA1 is one of three brain regions considered most susceptible to oxidative stress and various insults leading to rapid decline in its function [21,22]. Also, the DG, is another vulnerable brain tissue that contains adult neuronal stem cells which are responsible for adult hippocampal neurogenesis [23]. Caffeinated energy drinks are available worldwide and are frequently used to improve mood, physical performance and reduce mental fatigue [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hippocampal CA1 is one of three brain regions considered most susceptible to oxidative stress and various insults leading to rapid decline in its function [21,22]. Also, the DG, is another vulnerable brain tissue that contains adult neuronal stem cells which are responsible for adult hippocampal neurogenesis [23]. Caffeinated energy drinks are available worldwide and are frequently used to improve mood, physical performance and reduce mental fatigue [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is one of three brain regions that are most susceptible to oxidative stress and the first to undergo decline in its function [22]. The dentate gyrus (DG), is another vulnerable brain tissue that contains adult neuronal stem cells which are responsible for adult hippocampal neurogenesis [23].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the type and concentration, they strengthen or weaken synaptic morphology (141) and synaptic responses (142), leading to long-term potentiation (LTP) or long-term depression (LTD). Moreover, they can form new connections and pathways and can change the wiring of the circuits (143). In severe pathological conditions, physiological trophic effects will not provide sufficient tissue regeneration.…”
Section: Figure 7 |mentioning
confidence: 99%
“…The newly generated granular neurons in the DG region of the hippocampus are functionally integrated into the hippocampal circuit at 4 weeks [ 27 ]. Furthermore, the DG region is thought to play an essential role in learning, memory, and spatial navigation tasks [ 46 ], and previous studies demonstrated that neurogenesis in the DG region of the hippocampus can rescue the ability of learning and memory [ 33 , 51 , 52 ]. Our further study found that the number of BrdU + /NeuN + cells increased significantly on day 28, indicating that the number of newborn cells that survived and differentiated into neurons increased.…”
Section: Discussionmentioning
confidence: 99%